The Maternal Personhood of Cattle and Plants at a Hindu Center in the United States - Capper, Daniel (Pastoral psychology, 2016)
Religious experiences with sacred nonhuman natural beings considered to be 'persons' remain only vaguely understood. This essay provides a measure of clarification by engendering a dialogue between psychoanalytic self psychology on one side and, on the other, religious experiences of cattle and Tulsi plants as holy mothers at a Hindu cattle sanctuary in the United States. Ethnographic data from the Hindu center uncover experiences of sacred maternal natural beings that are tensive, liminal, and colored with affective themes of nurturance, respect, and intimacy, much like psychoanalytic maternal selfobjects. Devotees protect cattle and ritually venerate plants because these actions facilitate a limited experiential grounding of religiosity on what is perhaps the most fundamental of all relationships, the relationship with the mother, within a theological worldview that somewhat embraces nonhuman natural beings in both doctrine and practice.